Gerakan Sosial Baru di Kota Santri: Analisis Pandangan Gerakan Aliansi Aktivis dan Masyarakat Muslim Tasikmalaya (Almumtaz) Terhadap Ruang Bermusik 2025 - Muhammad Nurfikri; Nisa Khoerunisa; Faisal Fadilla Noorikhsan Faisal (Indonesian Democracy Research Center, 2026)
This study examines the dynamics of the Almumtaz religious social movement in the controversy surrounding the cancellation of several performers in the Ruang Bermusik 2025 concert in Tasikmalaya. It focuses on how Almumtaz operates as a social movement actor and how the “City of Santri” identity is constructed, maintained, and negotiated within the contemporary public sphere. This research employs a qualitative approach with a case study design, utilizing in-depth interviews, non-participant observation, and document analysis. The analytical framework draws on Sidney Tarrow’s social movement theory and Porta and Diani’s concept of collective identity. The findings reveal that Almumtaz mobilizes collective action rooted in religious values to challenge forms of popular culture perceived as inconsistent with local religious norms. The “City of Santri” identity functions not only as a cultural symbol but also as a political instrument institutionalized through local regulations to regulate public space. Furthermore, Almumtaz constructs a dynamic collective identity by transforming historical narratives of Islamic boarding schools and religious authorities into a source of social solidarity. This study highlights that local religious movements possess significant capacity to influence policy, shape the boundaries of cultural expression, and reproduce identity politics in the context of contemporary social change.